Whole genome sequence data of Bacillus anthracis strain 3B1 isolated from rice soil - Chan, Rosamond; Chua, Kah-Ooi; Teo, Kelly Wan-Ee; Prismantoro, Dedat; Suhaimi, Nurul Shamsinah Mohd; Ozturk, Abdullah Bilal; Rossiana, Nia; Doni, Febri (ELSEVIER, 2025)
Strain 3B1 was isolated from the soil of rice field cultivated under the system of rice intensification (SRI) in Sukabumi, West Java, Indonesia. The genome of strain 3B1 was sequenced using the MGI DNBSEQ platform, followed by bioinformatics processing, including genome assembly and gene annotation using SPAdes and Prokka, respectively. The assembled genome had a total length of 5,137,985 bp, distributed across 70 contigs, with 5,364 genes identified. Strain 3B1 shared the highest 16S rRNA gene sequence identity including Bacillus paranthracis, B. nitratireducens, B. cereus, B. paramycoides, B. tropicus, and B. anthracis, in the range of 99.86 to 99.93%. Both 16S rRNA gene and core genes-based phylogenetic analyses placed strain 3B1 in the same clade with B. anthracis strain Ames within the Bacillus genus. The phylogenetic placement was supported by the highest average nucleotide identity (ANI) value of 98.1% and digital DNA-DNA hybridization (dDDH) value of 82.7% shared between the genomes of B. anthracis strain Ames and strain 3B1, indicating that 3B1 is a strain of B. anthracis. Further gene an notation revealed that the genome of strain 3B1 lacked the genes encoding for virulence factors such as the pag, cya, and lef. Nonetheless, this data provides valuable insights into the genomic feature of strain 3B1, which can be bioprospected for various biotechnological applications. (c) 2025 The Author(s). Published by Elsevier Inc. This is an open access article under the CC BY license (http://creativecommons.org/licenses/by/4.0/)
Keywords: Bacillus anthracis; Genome annotation; MGI sequencing platform; Phylogeny; Rice; Whole genome sequencing; Science & Technology - Other Topics